A Study on Factors Influencing the Corporate Governance Practices in Listed Companies In India. - M.L.TomAntony, Mr.; D. Rajasekar, Dr. (International Journal of Engineering and Technology, 2018)
The role of individual investors/institutional investors in the general financial advancement of the nation has expected overpowering significance as the number shareholders both individual and institutional investors wind up voluminous. The role of substantial institutional investors in observing the execution of organizational management in India, in examination with other propelled nations on the planet. The reactions therefore uncovered that their part in the governing body gatherings, in helping better management hones, profitability, proficiency and viable working of the organization has been dissatisfactory. Hence,the key objective of the study are to find out the factors influencing the corporate governance practices in listed companies in India.The sampling technique used in this study is convenience sampling .In this study , preseumed that population size is finite and unknown; the formula was applied to know the sample size, and found that the sample size is 479.The overall analysis of this study reveals that an effective board to take responsible in improve the above factors in discharge the duties imposed by the law on the directors and increases the performance of corporate governance.Â